Performance evaluation of adaptive forwarding strategy using stochastic adaptive forwarding (SAF) in named data networking - Jemangin, Nor Faizah (2018)
In current IP-based network, loop is avoided by routing which have an authority in determining forwarding decision but it prevent efficiency of content dissemination. As future Internet architecture, NDN gives forwarding plane more authority by using forwarding strategy to improved Interest satisfaction ratio and cache hit ratio even in unexpected network status such as link failures. However, there are increased delay whenever simulation times, link failures or number of clients are increased. A number of technologies have been deployed in the current Internet infrastructure to accommodate the new demands for access to content such as Content Distribution Networks (CDN), Load Balancers, and Cloud Services. Although a lot of effort has been made to improved IP-based forwarding plane but it is confined to the data transmission in client-to-server mode or end-to-end. Thus, limiting the adaptability in the forwarding plane function. Unique characteristic of NDN over IP is the adaptability of its forwarding plane on choosing the potential outgoing face or forwarding link when it discovers link failure to achieve quick recovery and manage congestion by load balancing in multiple links. SAF has been introduced by Posch, Rainer & Hellwagner in 2017 as new forwarding strategy in NDN to increase the throughput by using adaptive ability in it. Thus, it gains my interest to study different perspective of performance such as delay and Interest retransmission in SAF using ndnSIM simulator. The result shows that Stochastic Adaptive Forwarding (SAF) is better than BestRoute in Interest satisfaction ratio by 17.8%, cache hit ratio by 1.8%, delay by 10.5 seconds and Interest retransmission by 22%. Result also shows BestRoute outperforms SAF in hop count by 3.2 hops because its aim is to find the shortest route to the cache or server without evaluating the link performance.